2019
DOI: 10.1021/acs.cgd.9b00410
|View full text |Cite
|
Sign up to set email alerts
|

Role of Racemization Kinetics in the Deracemization Process via Temperature Cycles

Abstract: A suspension of crystals of both enantiomers of a conglomerate forming chiral compound can be deracemized by applying temperature cycles in the presence of a racemizing catalyst that enables in solution the conversion of the undesired enantiomer into the desired one. We aim at showing through experiments that, seemingly paradoxically, accelerating the racemization reaction by increasing the catalyst concentration speeds up the deracemization process if all the other parameters are left unchanged. We prove this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(69 citation statements)
references
References 23 publications
4
63
2
Order By: Relevance
“…Overall racemization kinetics of our system seem therefore enhanced when using protic solvents with dielectric constant ɛ > 18, contrary to the system studied by Breveglieri et al [31] that showed a strong enhancement of the kinetics when using acetonitrile compared to isopropanol (which has a similar dielectric constant as propan-1-ol). In comparison, the rate constant in propan-1-ol is significantly higher than in acetonitrile.…”
Section: Influence Of Dbu Concentration On Racemization Ratecontrasting
confidence: 96%
See 3 more Smart Citations
“…Overall racemization kinetics of our system seem therefore enhanced when using protic solvents with dielectric constant ɛ > 18, contrary to the system studied by Breveglieri et al [31] that showed a strong enhancement of the kinetics when using acetonitrile compared to isopropanol (which has a similar dielectric constant as propan-1-ol). In comparison, the rate constant in propan-1-ol is significantly higher than in acetonitrile.…”
Section: Influence Of Dbu Concentration On Racemization Ratecontrasting
confidence: 96%
“…Brevegleri et al measured a rate constant of the same order (9.44 L.mol À 1 .min À 1 at 25°C in acetonitrile) for a similar compound, N-(2-methyl-benzylidene)-phenylglycine amide (NMPA) in a more polar solvent. [31] Thus, the kinetic model we propose for the racemization reaction of BnFTP in presence of DBU is confirmed by the experimental data. It is a first-order kinetic model similar to the one developed and validated by Brevegleri et al and in accordance with the literature.…”
Section: Influence Of Dbu Concentration On Racemization Ratesupporting
confidence: 73%
See 2 more Smart Citations
“…Comparing Figure 6(c) and (d) one can also see that a faster racemization reaction (higher R) leads to higher dimensionless productivities if the other parameters are equivalent. This is in agreement with recent literature on polythermal deracemization processes where the racemization kinetics were quantitatively investigated 41,42 . The authors of both studies concluded that a higher racemization rate leads to faster deracemization if the racemization reaction is rate-limiting.…”
Section: Effect Of Kinetics and Suspension Density On Process Performancesupporting
confidence: 92%